Computational investigation of Brownian motion and thermophoresis effect on blood-based casson nanofluid on a non-linearly stretching sheet - Zainal, Nurul Amira; Zuberi, Haris Alam; Lal, Madan; Verma, Shivangi (Penerbit Akademia Baru, 2024)
The present article investigates numerically the impacts of thermophoresis and Brownian motion on boundary layer nanofluid flow across a porous, non-linearly stretching sheet at a fixed temperature of the surface and under partial slip. Using the similarity variables, non-linear ordinary differential equations are obtained from the dictating partial differential equations, and then these non-linear ordinary differential equations are converted to a first order system of differential equations. The obtained first order system is then executed using bvp4c module in MATLAB along with the shooting technique. The numerical solutions obtained are scrutinized through graphs. It is observed that, as Nt and Nb levels rise, the temperature rises, and the thermal boundary layer thickens. Additionally, it has been found that the energy distribution expands, and nanoparticle concentration falls with rising values of the thermophoresis parameter.